Pengembangan Kemampuan Membaca Kitab dengan Metode Sorogan di Madrasah Assunniyyah Kencong Jember - Nafsah, Nor Holis bin; Royhan, Ahmad (An-Nuqthah, 2023)
The right method is one of the keys to the success of foreign language learning for students, especially Arabic. This research explores the process of mentoring and implementing the sorogan method in improving the ability to read the books of students of grade 6 ibtidaiyyah madrasah diniyyah assunniyyah kencong jember. and by applying this method, it is hoped that it can train students in improving the development of Arabic grammar, making it easier to read and understand the contents of the yellow book well. The research method used in this research is a qualitative method. This research concludes that the sorogan method gives significant results in triggering enthusiasm for learning and increasing the ability to read the yellow book of students in grade 6 ibtidaiyyah madrasah diniyyah Assunniyyah Kencong Jember.